2022
DOI: 10.1002/ehf2.13877
|View full text |Cite
|
Sign up to set email alerts
|

Different activation of MAPKs and Akt/GSK3β after preload vs. afterload elevation

Abstract: Aims Pressure overload (PO) and volume overload (VO) lead to concentric or eccentric hypertrophy. Previously, we could show that activation of signalling cascades differ in in vivo mouse models. Activation of these signal cascades could either be induced by intrinsic load sensing or neuro‐endocrine substances like catecholamines or the renin‐angiotensin‐aldosterone system. Methods and results We therefore analysed the activation of classical cardiac signal pathways [mitogen‐activated protein kinases (MAPKs) (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They showed that maladaptive cardiac hypertrophy in the afterload model was associated with apoptosis and fibrosis, whereas preload was associated with less apoptosis, better cardiac function, and no fibrosis [ 26 ]. Recently, Hartmann et al also reported the results of in vitro mechanical overload on ejection heart models in rabbit and human isolated muscle strips and found that selective afterload elevation results in ERK phosphorylation, whereas preload activates the AKT-GSK3β pathway, which plays a role in preventing cell apoptosis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that maladaptive cardiac hypertrophy in the afterload model was associated with apoptosis and fibrosis, whereas preload was associated with less apoptosis, better cardiac function, and no fibrosis [ 26 ]. Recently, Hartmann et al also reported the results of in vitro mechanical overload on ejection heart models in rabbit and human isolated muscle strips and found that selective afterload elevation results in ERK phosphorylation, whereas preload activates the AKT-GSK3β pathway, which plays a role in preventing cell apoptosis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%